Forecasting Penjualan Produk Sembako Menggunakan Metode Triple Exponential Smoothing - Toyib Hidayat, Asep; Puspita Sari, Dwi; Andriani, Pebrinda (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2024)
Forecasting is a very important factor in the decision making process. The forecasts made are generally based on the past which is then analyzed using certain methods. Past data is collected, researched, analyzed and linked to the passage of time. In this research, the Triple Exponential Smoothing Method is used, which is a forecasting method that is commonly used because it has simple concepts and calculations. One of the reasons for using the periodic series data smoothing method is because this method can be done with two approaches, namely the smoothing method and the exponential smoothing method. The results obtained from this research. Selecting the right ?, ?, ? values ??can produce ideal MAPE values. It is proven that to obtain ideal values ??for ?, ?, ? using the brute force method, the values ??obtained are ? = 0.1, ? = 0, 2, and ? = 0.9, we get a MAPE value of 1.92%, where previously the resulting MAPE was 7.54%.